On a spherical code in the space of spherical harmonics - Bondarenko, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We propose a new method for the construction of new “nice” configurations of vectors on the unit sphere S^d with the use of spaces of spherical harmonics.